2010
DOI: 10.1128/jvi.00110-10
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Rhesus Lymphocryptovirus MicroRNA Expression

Abstract: Rhesus lymphocryptovirus (rLCV) and Epstein-Barr virus (EBV) are closely related gammaherpesviruses that infect and cause disease in rhesus monkeys and humans, respectively. Thus, rLCV is an important model system for EBV pathogenesis. Both rLCV and EBV express microRNAs (miRNAs), several conserved in sequence and genomic location. We have applied deep sequencing technology to obtain an inventory of rLCV miRNA expression in latently rLCV-infected monkey B cells. Our data confirm the presence of all previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
50
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 67 publications
9
50
0
Order By: Relevance
“…Therefore, even differences of 1 nt at the 5Ј end potentially alter the target mRNAs. miRNA sequence heterogeneity has been observed in humans (45), Drosophila melanogaster (31), Caenorhabditis elegans (27), and herpesviruses, including KSHV (37), HSV (39), and rLCV (27). In all three of these herpesviruses, it was reported that 3Ј-end variation occurred more frequently than 5Ј-end variation (27,37,39).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, even differences of 1 nt at the 5Ј end potentially alter the target mRNAs. miRNA sequence heterogeneity has been observed in humans (45), Drosophila melanogaster (31), Caenorhabditis elegans (27), and herpesviruses, including KSHV (37), HSV (39), and rLCV (27). In all three of these herpesviruses, it was reported that 3Ј-end variation occurred more frequently than 5Ј-end variation (27,37,39).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have identified that miRNAs encoded by other herpesviruses associate with host silencing complexes (8,27). To confirm whether HCMV miRNAs are indeed incorporated into these complexes, we performed CLIP-seq (cross-linking and immunoprecipitation followed with high-throughput sequencing) experiments against Ago proteins for mock-infected and infected HFFs at 24 and 72 hpi (Fig.…”
Section: Global Statistics Of Short Cdna Libraries In Hcmv-infected Cmentioning
confidence: 99%
“…These small RNAs (smRNAs) are highly attractive from a viral standpoint in that they require minimal space within the genome and potentially offer a robust mechanism for specific targeting of host defense genes. HCMV is known to encode at least 11 miRNA precursors that are expressed and processed into mature miRNAs during infection (12).High-throughput sequencing approaches have been instrumental in recent viral miRNA studies, acquiring a level of resolution that was previously unachievable through cloning efforts (17,27,36). Deep-sequencing approaches have not been extended to smRNA analysis of HCMV-infected cells, and previous microarray-based studies were limited in assessing only host miRNA levels (30,37).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Northern blots were carried out as previously published (Riley et al 2010). The ebv-miR-BHRF1-2 and hsa-miR-16 miRNAs were probed with 59 phosphate radiolabeled TCAATTTCTGCCG CAAAAGATA and CGCCAATATTTACGTGCTGCTA, respectively.…”
Section: Northern Blotsmentioning
confidence: 99%